Natural antioxidants used in meat products: A brief review. (February 2019) - Ribeiro, Jéssica Souza; Santos, Maria José Missão Cordeiro; Silva, Larissa Kauly Rosa; Pereira, Luíza Carla Lavinscky; Santos, Ingrid Alves; da Silva Lannes, Suzana Caetano; da Silva, Marcondes Viana
Abstract: The lipoperoxidation and the oxidation of pigments and proteins reduces the quality and nutritional value of meat products. The use of antioxidants slows down this reaction, preserving the characteristics of the product during its storage and prolonging its useful life. The use of synthetic antioxidants in food products has been the subject of several toxicological studies. Currently, the call for antioxidants from natural sources stands out. Investigations in this sense should be conducted considering the complex mechanism of reactive oxygen species (ROS) and interactions with cellular constituents to elucidate the mechanism of action of synthetic antioxidants and natural sources. Although natural additives appear as an alternative to meet the various market niches and associate natural antioxidants to active packaging as they are progressively released into the product. In this review, we present research with natural antioxidants that could be used satisfactorily in meat products, in addition to recent studies that use them in active packaging.